Basketball jump shot technique design for high school athletes: Training method development - Sofyan, Davi; Budiman, Indra Adi (UIR Press, 2022)
This study aims to improve the results of basketball jump shot training through a study of the development of training methods. The research method used is development research. Development research that refers to the development model of Borg and Gall, namely: 1) preliminary study, 2) early development model, 3) expert evaluation, 4) small-scale trial, 5) product revision, 6) group trial, 7) refine the model, 8) define the final model. Data are collected using a questionnaire obtained from the evaluation of basketball experts and coaches, then tested with a small group of 12 athletes and a large-scale trial of 24 athletes. The data are the results of an assessment of product quality, suggestions for product improvement, and the results of filling out questionnaires by athletes. The data analysis technique used is descriptive percentage to reveal the athlete's assessment after using the product. The results of the validation of the development of training methods from basketball experts obtain an average percentage of 94.5%. While the validation of the development of training methods from basketball coaches obtain an average percentage of 96.2%. The results of the questionnaire that is filled out by 12 athletes are 21.7% who answering difficult, 46.7% answering moderately, and 31.6% answering easy. The results of the analysis of small-scale trial data from 12 athletes obtain an average percentage of 20.83% answering difficult, 50% answering moderate, and 29.16% answering easy. The results of the analysis of large-scale trial data from 24 athletes obtain an average percentage of 6.7% who answering difficult, 19.1% answering moderately, and 74.1% answering easy. From the available data, it can be concluded that the development of the basketball jump shot training method can be used for basketball athletes from SMA Negeri 1 Majalengka.